Tumor necrosis factor drives increased splenic monopoiesis in old mice. Issue 1 (1st April 2016) - Loukov, Dessi; Naidoo, Avee; Puchta, Alicja; Marin, Jorge L Arredondo; Bowdish, Dawn M E
Abstract : EMH in the spleen increases with age, in a TNF-dependent manner. Abstract: Aging is accompanied by changes in hematopoiesis and consequently in leukocyte phenotype and function. Although age-related changes in bone marrow hematopoiesis are fairly well documented, changes in extramedullary hematopoiesis are less well described. We observed that 18–22-mo-old mice had larger spleens than young controls and found that the enlargement was caused by increased monopoiesis. Because extramedullary hematopoiesis is often driven by inflammation, we hypothesized that the chronic, low-level inflammation that occurs with age is a causal agent in splenomegaly. To test this theory, we compared the number of monocytes in 18-mo-old tumor necrosis factor–knockout mice, which are protected from age-associated inflammation, and found that they did not have increased extramedullary monopoiesis. To determine whether increased splenic monopoiesis is caused by intrinsic changes in the myeloid precursors that occur with age or by the aging microenvironment, we created heterochronic bone marrow chimeras. Increased splenic monopoiesis occurred in old recipient mice, regardless of the age of the donor mouse, but not in young recipient mice, demonstrating that these cells respond to signals from the microenvironment. These data suggest that decreasing the inflammatory microenvironment with age would be an effective strategy for reducing inflammatory diseases propagated by cells of myeloid lineage, which increase in number with age.